(untitled) (Brazilian Journal of Oceanography, 2019)
Energy budgets for juvenile Pacific whiteleg shrimp, Litopenaeus vannamei (1.7-4.0 g ) fed with different diets were assessed. The energy partitioning between growth, respiration, ammonia excretion, feces and exuvia was calculated to estimate for total food energy intake. Shrimp oxygen consumption and ammonia excretion were quantified in sealed chambers (25°C, 34 ppt). Energy allocated for growth and feces were obtained from the wet combustion of whole body and feces samples, exuvia was estimated as 10% growth energy. Three diets were tested: 100% chopped fish (Fish), 100% commercial feed (Feed), and 50-50% chopped fish and commercial feed (Mix). Most of the energy from the diets was channeled into respiration (49.7-70.5%). Shrimp fed the Feed diet used more energy in growth (24.4%) than those fed Mix (13.4%) or Fish diets (13.2%), either in absolute (joule) or relative (% of ingested energy) terms. Conversely, energy loss as ammonia excretion was lower in shrimp fed Feed (1.0%) compared to shrimp fed Mix (4.2%) or Fish diets (7.8%). Less energy was lost in feces by shrimp fed Fish diet (7.3%) compared to Mix (20.2%) and Feed diets (22.2%). The calculated energy intake by shrimp fed Fish, Mix and Feed were 0.995, 1.100, and 1.255 kJ ind-1day-1, respectively. According to the O:N atomic ratios (oxygen consumed to nitrogen excreted), protein tented to be the predominant substrate catabolized by shrimp fed Fish (O:N=16±5.2), and Mix (O:N=25±11.6), with increasing use of carbohydrates and/or lipids in the Feed (O:N=74±37.3). Results suggest diet composition may affect energy budget and partitioning differently between metabolism and growth either in absolute or relative terms, as shrimp fed Fish and Mix diets used protein as main substrate for metabolism, whereas shrimp fed Feed diet channeled protein for growth, and lipids and carbohydrates for other metabolic functions.